The Role of Customer Sentiment Analysis in Enhancing Service Efficiency through Digital Transformation: Evidence from Coffee Shops in Manado - Abraham Patayoan; Samuel Rantung; Benny Lule (Jurnal Ilmu Multidisiplin, 2025)
This study examines the role of Customer Sentiment Analysis (CSA) in improving service efficiency in coffee shops in Manado, with a particular emphasis on the mediating function of digital transformation. Using a quantitative explanatory research design, data were collected from 180–200 coffee shop customers who actively engage with digital platforms such as online ordering systems, cashless payments, and social media interactions. Structural Equation Modeling (SEM) using SmartPLS was employed to test direct and indirect relationships among variables. The results show that CSA has a positive and significant effect on both digital transformation and service efficiency. Digital transformation also demonstrates a strong positive effect on service efficiency. The mediation analysis confirms that digital transformation significantly mediates the relationship between CSA and service efficiency, indicating that sentiment-driven insights enhance operational effectiveness when supported by digital technologies. This study contributes empirical evidence from the local coffee shop context, expanding prior research that has primarily focused on large companies and global service sectors. Practical implications suggest that small and medium-sized coffee shops can optimize service processes by leveraging sentiment data and digital tools to enhance customer experience and operational responsiveness.